Digital reading literacy, social reading motivation and social reading behavior of middle school students—an analysis based on the mediating effect model - Zhang, Wenyan; Wang, Ye; Jin, Longyun (Frontiers in Human Dynamics, 2025)
IntroductionSocial reading, which integrates the benefits of social interaction and value co-creation, has gained significant popularity among adolescents.MethodsThis study collected 2,347 valid survey responses from middle school students across Beijing, Shanghai, Guangzhou and Shenzhen. Based on this dataset, we developed and empirically validated a social reading behavior model featuring a mediating relationship.ResultsThe research specifically addressed the relative importance of digital reading literacy and social reading motivation in influencing social reading behavior. Our analysis revealed that when accounting for the mediating effect of social reading motivation, digital reading literacy demonstrates a stronger total effect on social reading behavior compared to the direct influence of social reading motivation. This finding suggested that digital reading literacy plays a pivotal role in shaping adolescents’ social reading practices, highlighting the need for focused attention on developing this competency to enhance overall reading quality.DiscussionThe implications of this study were twofold: theoretically, it contributed to our understanding of how to improve reading quality and cultivate positive digital reading habits among middle school students; practically, it offered valuable insights for educational institutions, policymakers, and social reading platform developers to optimize their approaches to adolescent literacy development.